Effectiveness of Activities Morning Circle to Increase Self-Confidence of 5-6 Year Old Children at ANNUR Kedungringin Islamic Kindergarten - Maulida, Luluq; R Agustinus Arum Eka Nugroho (Universitas Negeri Semarang, 2025)
Self-confidence or self-confidence is the attitude of every individual who feels confident in their abilities to be able to carry out an action without being influenced by others. Based on the results of initial observation data at ANNUR Kedungringin Islamic Kindergarten, self-confidence in children is still said to be low, namely 12%. This study aims to determine the effectiveness of Morning Circle Activities to Increase Self-Confidence in 5-6 Year Old Children at ANNUR Kedungringin Islamic Kindergarten and How Much Influence Morning Circle Activities Have to Increase Self-Confidence in 5-6 Year Old Children at ANNUR Kedungringin Islamic Kindergarten. This type of research is quantitative research, using an experimental method with a One Group Pre Test Post Test design. In this study, the population used as a sample was 24 students of class B of ANNUR Kedungringin Islamic Kindergarten who became the experimental class. Data collection techniques used observation and documentation. The results of this study indicate that morning circle activities are effective in increasing the self-confidence of children aged 5-6 years at ANNUR Kedungringin Islamic Kindergarten. This is proven by the results of the hypothesis test from the pre-test and post-test of the experimental class with the paired sample t-test proven by the results of Sig. (2-tailed) 0.000 <0.05, then Ho is rejected and Ha is accepted. It can be concluded that there is an average difference between the results of the Pre- test and Post-test studies through the N-Gain test, the results obtained are 0.611, which is in the moderate category.